The Gods of ancient Rome : religion in everyday life from archaic to imperial times - Turcan, Robert, 1929- (New York : Routledge, 2001)
"This is a vivid account of what their gods meant to the Romans from archaic times to late antiquity, and an exploration of the rites and rituals connected with them. After an extensive introduction into the nature of classical religion, the book is divided into three main parts: religions of the family and land; religions of the city; and religions of the empire. The book ends with the rise and impact of Christianity. Book jacket."--BOOK JACKET.
Includes bibliographical references (p. 167-174) and index.
Keywords: Gods, Roman; Mythology, Roman; Heroes -- Rome